ANTIOXIDANT, ANTIMICROBIAL ACTIVITY AND TOTAL PHENOL AND FLAVONOIDS ANALYSIS OF SAMBUCUS NIGRA (ELDERBERRY) - GOUD, N. SRINIVAS; PRASAD, GOBIND (International Journal of Current Pharmaceutical Research, 2020)
Objective: The goal of this study was paying attention on the chemical characterization of phytochemical compounds and their antioxidant activity of Sambucus nigra L. Methods: Phytochemical analysis was performed by Sambucus nigra L fruit extract. Total Phenol and Flavonoids content of elderberry fruit extract also determined using Folin-Ciocalteu colorimetric method and aluminum chloride colorimetric method. Antibacterial activity was performed by disk diffusion method and Antioxidant capacity was investigated by DPPH assay, butylhydroxytoluene used as a standard. Results: The richest anthocyanin in elderberry fruits was cyanidin-3-O-sambubioside. The antioxidant capacity obtained for elderberry extract proved that elderberry shown highest antioxidant activity, being the richest anthocyanins. The antioxidant capacity of elderberry fruit methanolic extract was recorded 62.56±1.12 percentages of scavenging activity. We also investigated antibacterial activity against four species Escherichia coli, Pseudomonas putida, Bacillus cereus, and Staphylococcus aureus. There E. coli was recorded 12.0 mm and Pseudomonas putida was recorded 0.34 mm zone of inhibition. Conclusion: The conclusion of our study is that Sambucus nisgra fruit extract has very high antioxidant activity which makes it recommendable for food industry and dietary supplement.